2020
DOI: 10.1590/0102-33062020abb0253
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of endophytic fungi in the leaflets and branches of Poincianella pyramidalis, an endemic species of Brazilian tropical dry forest

Abstract: Plants harbour diverse communities of fungal species in their internal compartments. Endophytic fungi help their hosts to establish, survive, and adapt to different environments. Here, we examined the diversity of endophytic fungi in the leaflets and branches of Poincianella pyramidalis, a plant species endemic to the Brazilian tropical dry forest (Caatinga). A total of 360 fragments of leaflets and branches were analysed and 189 endophytic fungi were isolated and distributed among 21 ascomycetous genera based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…In another study in the Atlantic Forest with plants of the same order (Myrtales) as that of M. mirabilis, similar Shannon indices ranging from 2.25 to 2.39 were found (Vaz et al 2014). In contrast to endophytic diversity in the Atlantic Forest, studies in the Caatinga forest showed lower diversity indices (Bezerra et al 2015;Oliveira et al 2020;Araújo-Magalhães et al 2021); however, Pádua et al (2018) recorded a higher diversity estimation (H' = 3.41) than our study when analysing the 'Brejo de altitude', an isolated fragment of humid forest (Atlantic Forest) found in the Caatinga forest. Although 88 % richness was recovered, more samples are needed to estimate the actual diversity of endophytic fungi.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In another study in the Atlantic Forest with plants of the same order (Myrtales) as that of M. mirabilis, similar Shannon indices ranging from 2.25 to 2.39 were found (Vaz et al 2014). In contrast to endophytic diversity in the Atlantic Forest, studies in the Caatinga forest showed lower diversity indices (Bezerra et al 2015;Oliveira et al 2020;Araújo-Magalhães et al 2021); however, Pádua et al (2018) recorded a higher diversity estimation (H' = 3.41) than our study when analysing the 'Brejo de altitude', an isolated fragment of humid forest (Atlantic Forest) found in the Caatinga forest. Although 88 % richness was recovered, more samples are needed to estimate the actual diversity of endophytic fungi.…”
Section: Discussionmentioning
confidence: 85%
“…Sequences of internal transcribed spacer (ITS) and intervening 5.8S rRNA, large subunit (LSU) rDNA, RNA polymerase II second largest subunit (rpb2), β-tubulin (tub2) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) were amplified using the primers ITS1/ITS4 or ITS5/ITS4 (White et al 1990), LR0R/LR5 (Vilgalys & Hester 1990;Vilgalys & Sun 1994), fRPB2-5F2/fRPB2-7cR (Liu et al 1999;Sung et al 2007), Bt2a/Bt2b (Glass & Donaldson 1995) and GDF1/GDR1 (Weir et al 2012), respectively. Amplification, sequencing, and sequence editing were performed according to the methodology described by Bezerra et al (2017) and Oliveira et al (2020). The sequences obtained in this study were deposited in the NCBI GenBank database (Table S1).…”
Section: Dna Extraction Pcr Amplification and Sequencingmentioning
confidence: 99%
“…The Brazilian Caatinga tropical dry forest extends for an area of 912,529 km² in Brazil and is the largest semiarid tropical ecoregion in South America (Marinho et al, 2019;Oliveira et al, 2020;Silva et al 2017). This is recognized as a Biosphere Reserve by UNESCO (2021).…”
Section: Research Context 1deforestation In Brazilmentioning
confidence: 99%